Legal Compliance and Dynamic Governance of School Operational Assistance Funds in Indonesia - Nur Ambia Arma; Yogi Suprayogi Sugandi; Rita Myrna; Dedi Sukarno (Khazanah Hukum, 2026)
Education plays a strategic role in national development, such as School Operational Assistance (SOA) program, which is legally governed by multi-ministerial regulations namely the Regulation of the Minister of Education, Culture, Research, and Technology Number 63 of 2023, the Minister of Finance Regulation number 204 of 2022, and the Minister of Home Affairs Regulation number 3 of 2023. While existing studies on SOA have largely focused on administrative accountability and financial effectiveness, ther have paid limited attention to how legal compliance operates within a fragmented, multi-actor governance structure and how adaptive governance mechanisms can address regulatory rigidity and compliance traps. This gap is particularly evident in complex urban contexts such as Jakarta. This study aims to analyze the level of legal compliance in the management of SOA funds and to develop a dynamic governance model that can improve legal compliance and the effectiveness of SOA management in Indonesia. The research uses a descriptive-qualitative approach supported by quantitative data, through surveys and questionnaires of 52 high schools (public and private), and also uses a normative-qualitative method through document analysis techniques of laws and regulations related to the implementation of SOA from the Minister of Education and Culture, Minister of Finance, and Minister of Home Affairs. The results show that 90% of schools reported timely or very timely SOA fund disbursement, and 92% considered the allocated funds sufficient or very sufficient to support operational needs. In terms of administrative capacity, 94% of schools reported no difficulty in financial reporting, indicating relatively strong procedural compliance. However, substantive challenges persist: 28% of respondents identified limited budget flexibility, 27% reported mismatches between allocations and actual school needs, and 18% experienced high administrative burdens due to dual system. From a legal compliance perspective, this study reveals that compliance is predominantly deterrence-based, driven by administratice obligation rather than normative understanding of regulatory objectives, increasing the risk of procedural compliance traps. The recommended model developed refers to three pillars of dynamic governance, namely Thinking Ahead (flexible and responsive planning), Thinking Again (continuous evaluation and simplification of procedures), and Thinking Across (collaboration between institutions and stakeholders). This model is expected to become a policy reference that is not only relevant to Jakarta but can also be adopted in other regions with similar characteristics in education finance management.